Malaysia's 13th general election: Sabah-Barisan Nasional fixed-deposit state? - Zaini Othman; Eko Prayitno Joko; Ramli Dollah; Amrullah Maraining; Kim, Jong Eop (2016)
As all are aware, the results of the Malaysia 12th General Election(GE-12) in 2008 have surprised many. Not only the dominant parties Barisan Nasional (BN) were shocked by the loss of significant numbers of seats but for the first time in the history of Malaysia politics, vis-à-vis, electoral affairs, they were denied a two-thirds majority in the Parliament. Notwithstanding the opposition parties such as Parti Islam Se-Malaysia (PAS), Democratic Action Party (DAP) and Parti Keadilan Rakyat (PKR: The People's Justice Party) that form the opposition coalition called Pakatan Rakyat (People's Alliance: PR), has come to a surprised with the GE-12 result, in which they not even think that were able to challenge hegemonic politics of BN, managed to capture and formed a government at the state level namely Kedah, Penang, Perak, and Selangor, except Kelantan which has been under the control of PAS since the 1990 general election. This article aims to analyze whether Sabah as a “fixed deposit”state is still relevant in understanding the continuity and survival of the BN political hegemony in the context of Malaysia political developments post-13th general election.